FAKTOR YANG MEMPENGARUHI KEJADIAN CARPAL TUNNEL SYNDROME PADA PERAJIN BATIK TULIS “SERULING ETAN” MAGETAN - Setyoaji, Dhaniswara; Jayanti, Siswi; Ekawati, Ekawati; Widjasena, Baju (Jurnal Kesehatan Masyarakat (Undip), 2017)
Improper workplace behavior is the main cause of Carpal Tunnel Syndrome. Carpal Tunnel Syndrome or secondary neurological diseases in the wrist, is a medical condition in which the central nervous depressed at the wrist resulting in patients experiencing numbness and weakness of the hand muscles. This research was conducted to determine the relationship between the factors that cause Carpal Tunnel Syndrome with incidence Carpal Tunnel Syndrome to the batik artisans at Seruling Etan. This research is an "explanatory research" with cross sectional approach. The population in this research are 40 artisans and samples used by 30 artisans working using canting. Data were collected by questionnaires, Tinel tests  and Phalen tests. The results showed that there was a relationship between the incidence of repetitive motion with Carpal Tunnel Syndrome (ρ Value = 0.003), there is a correlation between hand postures and the incidence of Carpal Tunnel Syndrome (ρ Value = 0.001), there is a correlation between age and the incidence of Carpal Tunnel Syndrome (ρ Value = 0.004), and there is a correlation between working period with the incidence of Carpal Tunnel Syndrome (ρ Value = 0.013). It is advisable for the worker to perform the stretch on the sidelines doing work on a regular basis.